Whole-body MRI with diffusion-weighted imaging: a valuable alternative to contrast-enhanced CT for initial staging of aggressive lymphoma. Issue 3 (March 2016) - Balbo-Mussetto, A.; Cirillo, S.; Bruna, R.; Gueli, A.; Saviolo, C.; Petracchini, M.; Fornari, A.; Lario, C.V.; Gottardi, D.; De Crescenzo, A.; Tarella, C.
Abstract : Aim: To compare the accuracy of whole-body magnetic resonance imaging (Wb-MRI) with diffusion-weighted imaging (DWI) to that of contrast-enhanced computed tomography (CE-CT) and 2-[ 18 F]-fluoro-2-deoxy-d- glucose ( 18 F-FDG) positron-emission tomography co-registered with low dose-CT (PET-CT) in defining lymphoma disease stage. Materials and methods: From February 2010 to May 2014, 41 lymphoma patients underwent Wb-MRI-DWI, CE-CT, and 18 F-FDG PET-CT. Histological subtypes included aggressive B-cell ( n =11), follicular ( n =13), mantle cell ( n =3), and Hodgkin's ( n =14) lymphoma. To compare the procedures, the reference standard (RS) assessment was defined by combining the results from 18 F-FDG PET-CT, CE-CT, and bone marrow (BM) histology, modifications after therapy, and histological re-assessments of uncertain lesions. Results: Among 1025 nodal sites, 217 had disease involvement according to the RS. CE-CT yielded 23 false-negative and 11 false-positive errors. Wb-MRI-DWI failed to recognise 17 localisations and had six false-positive errors; 18 F-FDG PET-CT had no errors. Among 458 extranodal sites, 37 were positive according to the RS. 18 F-FDG PET-CT yielded four false-negative and two false-positive results. CE-CT yielded 17 false-negative errors. Wb-MRI-DWI yielded a single false-negative error. Wb-MRI-DWI was the most reliable imaging technique for BM evaluation. Considering each procedure alone, the final stage would have been missed in four cases using 18 F-FDG PET-CT, 12 cases using CE-CT, and none using Wb-MRI-DWI. Conclusion: The present data support Wb-MRI-DWI as a sensitive and specific imaging technique for lymphoma evaluation, supporting its use in place of CE-CT for staging. Highlights: Recommended approach for staging lymphoma is 18F-FDG-PET with CT and BM biopsy. Wb-MRI-DWI is a new alternative technique to conventional radiation-based imaging. Wb-MRI-DWI is both sensitive and specific in staging malignant lymphoma.